2020
DOI: 10.1186/s40851-020-00164-6
|View full text |Cite
|
Sign up to set email alerts
|

Coloration principles of the Great purple emperor butterfly (Sasakia charonda)

Abstract: The dorsal wings of male Sasakia charonda butterflies display a striking blue iridescent coloration, which is accentuated by white, orange-yellow and red spots, as well as by brown margins. The ventral wings also have a variegated, but more subdued, pattern. We investigated the optical basis of the various colors of intact wings as well as isolated wing scales by applying light and electron microscopy, imaging scatterometry and (micro)spectrophotometry. The prominent blue iridescence is due to scales with tigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The functional structures of butterfly wing scales form during pupal development: scale cells grow protrusions that serve as templates for finely sculpted nanoscale cuticle morphologies ( 1 3 ). By tailoring these scale morphologies, butterflies produce unique visual appearances ( 4 7 ), ensure thermal regulation ( 8 ) and water repellency ( 9 ), or generate beneficial acoustic ( 10 ) and aerodynamic effects ( 11 ). Interdisciplinary interest in these material functionalities has led to scientific advances in the comprehensive assessment of the scales’ multifunctional material properties ( 12 ), design of next-generation bioinspired functional materials ( 13 , 14 ), identification of key genes in patterning and structural color ( 15 19 ), and evaluation of the impact of ecological factors on biodiversity ( 20 , 21 ).…”
mentioning
confidence: 99%
“…The functional structures of butterfly wing scales form during pupal development: scale cells grow protrusions that serve as templates for finely sculpted nanoscale cuticle morphologies ( 1 3 ). By tailoring these scale morphologies, butterflies produce unique visual appearances ( 4 7 ), ensure thermal regulation ( 8 ) and water repellency ( 9 ), or generate beneficial acoustic ( 10 ) and aerodynamic effects ( 11 ). Interdisciplinary interest in these material functionalities has led to scientific advances in the comprehensive assessment of the scales’ multifunctional material properties ( 12 ), design of next-generation bioinspired functional materials ( 13 , 14 ), identification of key genes in patterning and structural color ( 15 19 ), and evaluation of the impact of ecological factors on biodiversity ( 20 , 21 ).…”
mentioning
confidence: 99%
“…Second, by revealing a general law between ridge height and color hue, our findings shed new light on a new causative mechanism of structurally colored ridges across nymphalids 30,32,33,34,35 , pierids 36,37 , and lycaenid butterflies 38 . In many of these species the ridges have a Christmastree-like, or Morpho type, structure 39,8 , whose prominent side lamella were thought to be the main color-generating features 8,40,30,41,31 .…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, in many butterfly species, the dorsal and ventral wing sides appeared to be similarly colored and patterned, which suggested that in those cases, the ventral wing coloration is also part of the butterfly’s display. For example, in the common bluebottle Graphium sarpedon Linnaeus, 1758 [ 23 ] and the great emperor butterfly Sasakia charonda Hewitson, 1863 [ 24 ], the dorsal and ventral wing patterns strikingly resemble each other, and in transmitted light, virtually the same patterning is observed as that in reflected light. The possible contribution of transmitted light to wing coloration has so far received little attention, although it may play an important role in a butterfly’s visual signaling.…”
Section: Introductionmentioning
confidence: 99%